STIMULUS KEAKTIFAN SISWA MELALUI PENERAPAN MEDIA INTERAKTIF PADA PEMBELAJARAN MATEMATIKA SECARA DARING [STIMULATING THE ACTIVENESS OF STUDENTS THROUGH THE IMPLEMENTATION OF INTERACTIVE MEDIA IN ONLINE MATHEMATICS LEARNING] - Manoi, Gledis; Soesanto, Robert Harry (Universitas Pelita Harapan, 2022)
The activeness of students is important and fundamental to support the effectiveness of online mathematics learning. However, the reality shows that students often lack courage and enthusiastism in asking and answering questions, conveying understanding, and being less involved in doing assignments. Some of these indicate that students are less active in learning mathematics online. One of the efforts that teachers can make is through the application of various interactive media. Therefore, this paper aims to review and examine the implementation of various interactive media as an effort to stimulate the activeness of the students in online mathematics learning. Using descriptive qualitative research methods, it is evident that the implementation of various interactive media can enourage students to be active in online mathematics learning. The implementation of various interactive media make students pay attention, so they can be encouraged to be actively involved in the learning process. Thus, students can be led to maximaze themselves in every opportunity to glorify God, including in the mathematics learning process. In the application of interactive media, teachers are advised to record every development of student responses for the improvement and development of interactive media.BAHASA INDONESIA ABSTRACT: Keaktifan siswa menjadi hal penting dan mendasar yang dapat menunjang keefektifan pembelajaran matematika secara daring. Namun, kenyataan menunjukkan bahwa siswa sering kurang berani dan antusias dalam bertanya, menjawab, menyampaikan pemahaman, serta kurang terlibat dalam mengerjakan tugas. Beberapa hal tersebut menunjukkan bahwa siswa kurang aktif dalam pembelajaran matematika secara daring. Salah satu upaya yang dapat dilakukan guru dalam mendorong keaktifan siswa adalah melalui penerapan media interaktif yang bervariasi. Olehnya tulisan ini bertujuan meninjau dan mengkaji penerapan media interaktif sebagai upaya yang dapat menstimulus keaktifan siswa pada pembelajaran matematika secara daring. Melalui metode kualitatif deskriptif, diketahui bahwa penerapan media interaktif yang bervariasi dapat mendorong siswa menjadi aktif dalam pembelajaran matematika secara daring. Media interaktif yang bervariasi menarik perhatian siswa sehingga mendorong siswa terlibat aktif dalam pembelajaran. Dengan demikian, siswa dapat dituntun untuk memaksimalkan diri dalam setiap kesempatan untuk memuliakan Allah, termasuk dalam pembelajaran matematika. Dalam penerapan media interaktif, guru disarankan mencatat setiap perkembangan respon siswa guna perbaikan dan pengembangan media interaktif.